The Use of Unaltered Appendix Transfer in Ileal Continent Reservoir: 10 Years Experience, A Novel Technical Modification - Simforoosh, Nasser; Basiri, Abbas; Ziaee, Seyed Amir Mohsen; Sharifiaghdas, Farzaneh; Tabibi, Ali; Javaherforooshzadeh, Ahmad; Sarhangnejad, Reza; Moudi, Emad-Adin; Tajali, Farzad (Urology Journal, 2009)
Introduction: We report a new modified technique of unaltered appendix transfer to ileal pouch and preserving ileocecal segment. This modification enables us to use ileum as the popular type of enteric segment instead of ileocecal segment while using appendix as a catheterizable stoma. Materials and Methods: Forty-five patients (30 men) who needed reconstruction of the lower urinary tract were enrolled for using appendix as a catheterizable stoma. Reservoir was reconstructed using ileal segment. The appendix was circumcised from its base over its pedicle. The spatulated appendix tip was exteriorized as a catheterizable stoma to the skin, preferably umbilicus, and its base was implanted to the ileal pouch.Results: Follow-up records of 38 of 45 patients were available. The median follow-up period was 29 months. The mean intermittent catheterization interval was 4.19 Â± 1.6 hours. Urodynamic parameters were evaluated for 18 out of 38 patients. The median maximal pouch capacity determined as 380 mL. The median appendiceal closure pressure was 61 cm H2O. No pouch perforation occurred. Stomal stenosis occurred in 3 patients. They did not catheterize their appendiceal stoma because they restarted catheterization through the urethra. Conclusion: This novel approach enabled us to use ileum as today's more popular type of bowel segment to reconstruct enteric pouch rather than using ileocecal segment, while using appendix as a catheterizable stoma. One of the unique advantages of this technique is that the postponement of clean intermittent catheterization will not result in pouch perforation since the urine will leak when the pouch becomes overfill.